Effect of Light Availability on the Interaction between Maritime Pine and the Pine Weevil: Light Drives Insect Feeding Behavior But Also the Defensive Capabilities of the Host - Suárez-Vidal, Estefanía; López-Goldar, Xosé; Sampedro, Luis; Zas, Rafael (Frontiers in Plant Science, 2017)
Light is a major environmental factor that may determine the interaction between plants and herbivores in several ways, including top-down effects through changes in herbivore behavior and bottom-up effects mediated by alterations of plant physiology. Here we explored the relative contribution of these two regulation processes to the outcome of the interaction of pine trees with a major forest pest, the pine weevil (Hylobius abietis). We studied to what extent light availability influence insect feeding behavior and/or the ability of pines to produce induced defenses in response to herbivory. For this purpose, three-year old Pinus pinaster plants from three contrasting populations were subjected to six days of experimental herbivory by the pine weevil under two levels of light availability (complete darkness or natural sunlight) independently applied to the plant and to the insect in a fully-factorial design. Light availability strongly affected the pine weevil feeding behavior. The pine weevil fed more and caused larger feeding scars in darkness than under natural sunlight. Besides, under the more intense levels of weevil damage (i.e. those registered with insects in darkness), light availability also affected the pine’s ability to respond to insect feeding by producing induced resin defenses. These results were consistent across the three studied populations despite they differed in weevil susceptibility and inducibility of defenses. Morocco was the most damaged population and the one that induced more defensive compounds. Overall, results indicate that light availability modulates the outcome of the pine - weevil interactions through both bottom-up and top-down regulation mechanisms.